Code generation for embedded real time system - Talab, Mahmood Aghajani Siroos (2010)
Applying simple and reuse software to Embedded Real Time systems poses significant challenges to industrial software which is applicable for large expert domain. ERT Software development is complex due to multidisciplinary knowledge required the development method such as software engineer, mechanical engineer and electrical engineer. So, users of ERT software development framework are not limited to designers and developers who have software engineer background. The developed framework consists of three main elements: a modified component model, a component based timing analysis approach, and a code generator. An important part of the ERT framework which helps to develop ERT system is called code generator. Most of the code generators which are implemented by ERT frameworks can not represent complexity of ERT system. Currently many Object Oriented Analysis and Desigin methodology are available for implemenation of code generators, but their model cannot support ERT Component Base Development(CBD) directly. This motivate the study to propose criteria to evaluate exiting ERT frameworks, Then code generation in support CBD. This study consider further two important criteria which are Large Scale and Iterative development to be integrated with a Component Oriented Programing (COP) by developing a code generation tool. Thus, in this research a new tool was developed to support CBD framework method for ERT systems. To evaluate the applicability of the new tool, an ERT Case Study was designed and developed. Important features of COP and a commercial tool wich is called Rational Rose are compared based on a case study in this research. The result showed the advantages of COP code generation for supporting CBD method